Rockburst prediction and stability analysis of the access tunnel in the main powerhouse of a hydropower station based on microseismic monitoring. (February 2020) - Xue, Ruixiong; Liang, Zhengzhao; Xu, Nuwen; Dong, Linlu
Abstract: The access tunnel in the main powerhouse of the Shuangjiangkou hydropower station in China has complex geological conditions and is subject to high in situ stress in deep buried sections. Microseismic activity in the surrounding rock mass of the tunnel was monitored by a microseismic monitoring system, and rockburst was effectively predicted. Based on abundant data obtained from the microseismic monitoring, statistical parameters, which include cumulative apparent volume, the energy index, cumulative released energy and the Es/Ep value, were used to analyze the microseismic activity before and after rockburst to determine a more accurate early warning period and construction safety period. A sharp decrease in the energy index and a rapid increase in the cumulative apparent volume indicated a deterioration of the surrounding rock mass stability. The change characteristics of Es/Ep values revealed that the rockburst process underwent a transformation of compression-shear damage, tension-shear mixed damage and tension damage. Finally, based on the number of daily events N and the b value of the microseismic events, lg N / b was first established to evaluate the rockburst risk of tunnels. When the value of lg N / b was greater than 1, rockburst was more likely to occur; the larger the lg N / b value, the more severe the rockburst was. The research results provide an important reference value for the prediction of rockbursts in deep tunnels and the regulation of site construction progress.